Sistem Pemantauan Pertumbuhan Anggrek Berdasarkan Pengolahan Citra Digital - Magnolia Gina Ro'fataka Satriorini; Raden Sumiharto; Roghib Muhammad Hujja (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2022)
Growth monitoring and plant protectionis the major aspect of horticulture because its productivity depends on the health of the plants. Manual direct measurement methods tend to be destructive towards observed plants. In this research, a smart non-contact growth monitoring system was implemented on a chamber with orchid plants asthe objectsobserved. The images of the orchids were taken and became the input of the system to be processed to estimate the height of the plants.The contour of the orchid plant as the object was obtained and the height was calculated based on the highest and the lowest contour.The result shows that the developed system is proven to be capable of measuring orchid’s height in real-time with accuracy more than 95,7%. Thus, this system will effectively help farmers to improve the quality and the quantity of the plant’s productivity.